Synergistic remediation of cadmium and BDE-209 co-contaminated soil using Solanum nigrum assisted by Arbuscular mycorrhizal fungi and citric acid - Li, Hanhao; Zhou, Rujun; Li, Danyu; Chen, Xun Wen; Mo, Cehui; Li, Hui (Frontiers in Microbiology, 2025)
Co-contamination of cadmium (Cd) and polybrominated diphenyl ethers (PBDEs) in soil is common, posing serious ecological and health risks. Simultaneous remediation of both pollutants using plants is particularly challenging due to their contrasting environmental behaviors. The challenge is chelators can enhance Cd extraction by plants but Cd inhibits microbial activity, limiting PBDEs degradation. To tackle this, arbuscular mycorrhizal (AM) fungi show promising potential as they produce extensive hyphae networks capable of immobilizing Cd and enhancing rhizosphere microbial activity. However, the combined effects of AM fungi and chelators for the simultaneous remediation remain elusive. Here, using a pot experiment, Solanum nigrum was grown in Cd/BDE-209 co-contaminated soil under four treatments (control, citric acid, AM fungi, and combined) to assess remediation potential. we found that CA increased ethanol-extractable Cd in shoots by 2.81-fold while reducing shoot total Cd concentration by 19.91%. Additionally, CA enhanced BDE-209 accumulation by 40.75% but decreased biomass by 20.22%. AM fungi increased the proportion of residual Cd in shoots, which thereby reduced Cd toxicity to plants, and enhanced the proportion of acid-soluble Cd in soil, promoting Cd mobilization. However, these changes did not affect the remaining Cd or BDE-209 concentrations in the soil. The combination of AM fungi and CA reduced soil Cd concentration by 13.09% compared to the control and promoted BDE-209 accumulation in S. nigrum shoots, resulting in a 42.80% decrease in soil BDE-209 concentration. This reduction was attributed to enhanced soil polyphenol oxidase and urease activities, which accelerated BDE-209 debromination and dissipation. Our work shows the synergistic potential of AM fungi and CA in mitigating Cd and PBDEs co-contamination, offering a sustainable remediation strategy.